The BPI Process and its epistemological specificities - Campos, Flávio; Rodrigues (Universidade Estadual de Campinas – UNICAMP, Campinas/SP, Brazil), Graziela Estela Fonseca (Revista Brasileira de Estudos da Presença, 2022)
In this article, we present some aspects of Dancer-Researcher-Performer (BPI) method that can be considered in its epistemological specificities. Therefore, the first purpose is to present a bibliographic review of this training and scenic creation methodology that has been developed for over thirty years in Brazil. Through brief reports, we present the history of the BPI, we describe its creative process and we list some data that enable a better understanding of this method, its singularities in the performing arts field. This paper does not intend to exhaust this subject, but rather seeks to open spaces for new dialogues and debate.